Barriers to Professional Mental Health Help-Seeking Among Chinese Adults: A Systematic Review - Shi, Wei; Shen, Zhuozhuo; Wang, Siyuan; Hall, Brian J. (Frontiers in Psychiatry, 2020)
Background: A large number of Chinese suffer from common mental disorders (e.g. depression, anxiety, stress, and post-traumatic stress disorder), but treatment seeking is typically low in this population. It is unclear what barriers influence professional mental health help-seeking behavior within the Chinese population. Identifying these barriers could assist in implementation science efforts to reach this population. Objective: This review systematically synthesizes findings related to the barriers to professional mental health help-seeking among Chinese adults. Methods: Two English language databases (PubMed and PsycINFO) and two Chinese databases (WANFANGDATA and CNKI) were searched to find relevant studies. Quality assessment was conducted in identified studies. Quantitative findings were tabulated and frequently reported barriers were ranked. Primary data obtained from qualitative studies were thematically analyzed. Results: Of 6933 citations identified, 17 met inclusion criteria. There were 11 (64%) studies that reported quantitative methods; 3 (18%) employed qualitative research, and 3 (18%) mixed methods. Results indicated that frequently reported barriers to mental health help seeking among Chinese adults included a preference for self-reliance, seeking help from alternative sources, low perceived need toward help-seeking, a lack of affordability, negative attitude toward, or poor experiences with help-seeking. Less frequently mentioned barriers included stigma, families' opposition, limited knowledge about mental illness, a lack of accessibility, unwillingness to disclose mental illness, and fear of burdening family. Conclusions: The current review identified a number of key barriers to help-seeking behavior. Effective strategies are needed to promote professional help-seeking among Chinese adults. Additional factors influencing professional mental health help-seeking need to be further investigated, as they may contribute to a better understanding of ​the help-seeking behavior among Chinese.